2008
DOI: 10.1126/science.1157980
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Electron Tunneling and Diffraction

Abstract: Molecular structure is usually determined by measuring the diffraction pattern the molecule impresses on x-rays or electrons. We used a laser field to extract electrons from the molecule itself, accelerate them, and in some cases force them to recollide with and diffract from the parent ion, all within a fraction of a laser period. Here, we show that the momentum distribution of the extracted electron carries the fingerprint of the highest occupied molecular orbital, whereas the elastically scattered electrons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
522
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 742 publications
(533 citation statements)
references
References 34 publications
8
522
1
2
Order By: Relevance
“…This phenomenon, 'laser-induced recollision', enables new measurement techniques: photorecombination leads to attosecond pulse production [9] whereas elastic and inelastic electron rescattering offer new approaches to diffraction imaging. [2,10,11] In typical experiments, the electron has acquired up to 100 eV of kinetic energy during its transit in the continuum and can release it in the form of an attosecond pulse. Since the emission takes place around each zero-crossing of the field, the described mechanism generates a train of attosecond pulses separated by half the period of the generating laser field.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon, 'laser-induced recollision', enables new measurement techniques: photorecombination leads to attosecond pulse production [9] whereas elastic and inelastic electron rescattering offer new approaches to diffraction imaging. [2,10,11] In typical experiments, the electron has acquired up to 100 eV of kinetic energy during its transit in the continuum and can release it in the form of an attosecond pulse. Since the emission takes place around each zero-crossing of the field, the described mechanism generates a train of attosecond pulses separated by half the period of the generating laser field.…”
Section: Introductionmentioning
confidence: 99%
“…This would also allow us to compare the alignment dependence of single-photon PI by soft X-ray with multiphoton ionization by IR lasers [194,195]. In Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Combining conventional electron or X-ray beam methods with femtosecond laser pulses provides improved temporal resolutions for molecular dynamics investigation approaching atomic time scales [23][24][25][26] . However, recent experiments [27][28][29][30][31] demonstrated that intense, isolated femtosecond pulses alone are sufficient for imaging simple molecules via a strong-field three-step process 32,33 (see Supplementary Discussion). First, the intense, low-frequency laser ionizes the molecule.…”
mentioning
confidence: 99%
“…Conceptually this is analogous to the external electron beam used in conventional electron diffraction (CED) studies. Dubbed laser-induced electron diffraction (LIED) 34,35 , the method relies on extracting elastic differential cross-sections (DCS) from the two-dimensional (2D) photoelectron angular distributions [27][28][29][30][31] . Recently, picometre and femtosecond resolutions were demonstrated for N 2 and O 2 bond distance determination by fitting the extracted angledependent elastic DCS 36 .…”
mentioning
confidence: 99%